And we stay - Hubbard, Jenny (New York : Delacorte Press, 2014)
Sent to an Amherst, Massachusetts, boarding school after her ex-boyfriend shoots himself, seventeen-year-old Emily expresses herself through poetry as she relives their relationship, copes with her guilt, and begins to heal.
Grades 9-12.
Keywords: Boarding schools -- Juvenile fiction; Printz Honor Award; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Suicide -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Poetry -- Juvenile fiction; Amherst (Mass.) -- Juvenile fiction; Novels in verse; Boarding schools -- Fiction; High schools -- Fiction; Schools -- Fiction; Suicide -- Fiction; Interpersonal relations -- Fiction; Poetry -- Fiction; Amherst (Mass.) -- Fiction; Young adult fiction